Data Cad / For the Architect - Buehrens Carol; Tab Books (1989)
This book introduces the architect to the World of Computer-Aided Design (CAD), using sophisticated DataCAD Software. Acknowledgements, Overview, Beginning Data CAD, Basic Drafting Techniques, Windowing, Adding Symbols, Plotting Your Drawing, Creating Initial Site Plans, Copying Techniques, Detail Drawings, Creating Templates and Symbols, Creating Your Default Drawings, Final Exercises, Index.